Political-Management Decisions and Some Characteristics of its Modeling - Ulug’bek Hayitov (Periodica Journal, 2023)
The article covers political-administrative decisions, its functions, the decision-making process, the characteristics of the activity of governing bodies in political processes, decision-making and stages, selection and evaluation, qualifications, methods, models, and some of the importance of modeling.
Keywords: Socio-political life; political processes; management; management purpose